Gender Disparity, Education and Empowerment; Implications for Sustainable Development: A Case of South Ethiopia Public Universities (British Journal of Multidisciplinary and Advanced Studies, 2022)
Mean scores respectively showed that, empowerment is a multidimensional concept, which purports to measure a woman’s ability to control resources, her ability to choose and control different outcomes, getting social acceptance, and above all to enhance her self-esteem. Education as very important tools in the realization of empowerment, and maintain parity. Since it significantly matters to the broad-based development agendas of the country, the main objective of this study is critically explore gender disparity, education and empowerment in Southern Ethiopia higher institutions. In order to answer the basic research questions, this study were employed cross-sectional survey and correlation research design. On the other hand, the study used a concurrent mixed approach, in which both the qualitative and quantitative data were generated from the respondents at the same time. Moreover, the study was quantitative dominant qualitative. The current study conducted on three public Universities (Hawassa, Arbaminch, and Wolaita). In the due course, a multi stage sampling technique were used to draw the necessary sample size for the study. Based on this technique, a total of 341respondents were taken and the sample size determination focuses on 95 % confidence level and within 5 % confident limit. In the latter case, descriptive analysis was carried out. This includes average mean, standard deviation. Pearson product moment correlation based on the level of measurements of the variables were used to check the inter items correlation. Two-sample t-testwere used to see mean difference among variables. Chi-squared test were also used to see the relationship between two categorical variables. One way ANOVA were used to see the variations between and within groups by considering its assumptions. Moreover, binary logistic regression model adopted to determine the relationship between a binary dependent variable (empowered or disempowered) and a set of independent variables at Beta label (β). From the results of this study, it can be said that despite the fact that improvement in women education, monthly incomes;the level of empowerment in their economic, socio-cultural, legal and political dimensions is not significant as compare to their counterpart. The t-test result reveals, there is statistically significant mean difference in females’ academic rank and their participation in different positions of the university at 0.01 % and 0.05 % significant level respectively. Furthermore, there is statistically significance relationship between empowerment and education. In nutshell, in this study it is investigated that the level of women empowerment based on five empowerment dimensions were at a very infant stage at the sample universities. Thus, to effective gender parity and economic, socio-cultural, legal, political and psychological empowerment the researcher recommended different strategic pillars.
Keywords: Development; Disparity; Education; Empowerment; Gender